Plant fibers as alternatives to mineral fillers in thermoplastic composites – Ford’s vision or Al Gore’s? - Kijeński, J.; Kijeńska, M.; Osawaru, O. (Polimery, 2021)
An extensive analysis of the possibilities and goal in the application of composites as an alternative to thermoplastic polymer composites filled with minerals has been presented. The analysis was made taking into special consideration the mechanical properties and applicability of polypropylene composites, which are widely used and well characterized. It was shown that the enthusiasm and expectations linked with the vision of the application of thermoplastics filled with plant fibers from widely available renewable sources as cheap materials with attractive properties has not been fully justified. The realistic solution would be maintaining the production of these new materials derived from waste polyolefins and renewable fiber materials from agriculture and forestry industries for low-end applications.